CONSCIENTIOUSNESS, KEBERSYUKURAN, DAN PSYCHOLOGICAL WELL-BEING PADA ORANGTUA DENGAN ANAK BERKEBUTUHAN KHUSUS - Amelia Sari; Nurul Qomariyah (Jurnal Psikologi, 2023)
Mentally healthy individuals can face all the challenges of life effectively. One of the indicators of mental health is the presence of psychological well-being. Parents who have children with special needs need to have high psychological well-being. The purpose of this study was to determine the effect of conscientiousness and gratitude on psychological well-being on parents of children with special needs. This research is a quantitative study using Ryff's psychological well-being scales, Gratitude Questionnaire-6 (GQ-6), and conscientiousness taken from the HEXACO-PI-R scale. The subjects in this study were selected using a purposive sampling technique with a total of 55 parents who have children with special needs. The hypotheses were analyzed using multiple regression analysis. The results of this study indicate that conscientiousness and gratitude have a simultaneous effect of 62% on psychological well-being in parents who have children with special needs. However, among the conscientiousness variables and the gratitude variable which has the most dominant influence on psychological well-being is the gratitude variable.